The EGFRvIII transcriptome in glioblastoma: A meta-omics analysis. Issue 3 (5th October 2021) - Hoogstrate, Youri; Ghisai, Santoesha A; de Wit, Maurice; de Heer, Iris; Draaisma, Kaspar; van Riet, Job; van de Werken, Harmen J G; Bours, Vincent; Buter, Jan; Vanden Bempt, Isabelle; Eoli, Marica; Franceschi, Enrico; et al.
Abstract: Background: EGFR is among the genes most frequently altered in glioblastoma, with exons 2-7 deletions ( EGFRvIII ) being among its most common genomic mutations. There are conflicting reports about its prognostic role and it remains unclear whether and how it differs in signaling compared with wildtype EGFR . Methods: To better understand the oncogenic role of EGFRvIII, we leveraged 4 large datasets into 1 large glioblastoma transcriptome dataset (n = 741) alongside 81 whole-genome samples from 2 datasets. Results: The EGFRvIII/EGFR expression ratios differ strongly between tumors and range from 1% to 95%. Interestingly, the slope of relative EGFRvIII expression is near-linear, which argues against a more positive selection pressure than EGFR wildtype. An absence of selection pressure is also suggested by the similar survival between EGFRvIII -positive and -negative glioblastoma patients. EGFRvIII levels are inversely correlated with pan- EGFR (all wildtype and mutant variants) expression, which indicates that EGFRvIII has a higher potency in downstream pathway activation. EGFRvIII -positive glioblastomas have a lower CDK4 or MDM2 amplification incidence than EGFRvIII -negative ( P = .007), which may point toward crosstalk between these pathways. EGFRvIII -expressing tumors have an upregulation of "classical" subtype genes compared to those with EGFR -amplification only ( P = 3.873e −6 ). Genomic breakpoints of the EGFRvIII deletions have a preference toward the 3′-end of the large intron-1. These preferred breakpoints preserve a cryptic exon resulting in a novel EGFRvIII variant and preserve an intronic enhancer. Conclusions: These data provide deeper insights into the complex EGFRvIII biology and provide new insights for targeting EGFRvIII mutated tumors.